(untitled) (Research, Society and Development, 2024)
Introduction: Sports dietary supplements promote improvement in physical activity by providing nutrients. In pursuit of overall body development, the sports supplements market has been growing in popularity, leading to increased consumption and consequently, hindering the reliability of available information about supplements. The use of supplements without scientific evidence and in an abusive manner can lead to harm to individuals. Objective: To analyze the efficacy of dietary supplements aimed at enhancing performance. Methodology: Literature review using scientific articles and legal documents published from 2013 to 2024, utilizing databases and websites such as EBSCO, PubMed, Ministry of Health, ANVISA, and the Brazilian Society of Sports Medicine and Exercise. Results and conclusion: The most commonly used supplements by athletes and exercisers are creatine, whey protein, BCAA, glutamine, and maltodextrin. However, users’ knowledge about the correct use of these supplements is limited, and professionals in the field lack sufficient specialization. Therefore, further investigation is necessary to better understand the consumption of these supplements.